Do consumers select food products based on carbon dioxide emissions? Evidence from a buying experiment in Japan - Keiko Aoki (Osaka University, Institute of Social and Economic Research (ISER), 2009)
This study investigates how consumers value carbon dioxide (CO2) emissions of food by conducting a choice experiment before an ecolabel is attached on some foods in Japan. Participants are asked to buy some Satsuma mandarin oranges based on price and CO2 emissions and take them home. The following results are obtained: (i) the willingness-to-pay (WTP) estimate for the reduction of 1 g CO2 emissions per 100 g of Satsuma mandarin oranges is 0.417 JPY; (ii) people below 30 years, who are significantly conscious about the environment, do not choose Satsuma mandarin oranges based on CO2 emissions and have less value for this; and (iii) people above 30 years, who are environmentally friendly, choose the oranges based on price and have more value for this, although this implies that they do not relate food to CO2 emissions. Thus, since whether or not people select food based on CO2 emissions differs across ages, each age group has a different approach to reducing the CO2 emissions of food.
Keywords: C91; Q18; Q54; 330; carbon dioxide emissions; choice experiment; consumer preference; ecolabeling; food labeling; fruit